Colonization of Abandoned Land by Juniperus thurifera Is Mediated by the Interaction of a Diverse Dispersal Assemblage and Environmental Heterogeneity - Escribano-Avila, Gema; Sanz-Pérez, Virginia; Pías, Beatriz; Virgós, Emilio; Escudero, Adrián; Valladares, Fernando (PLOS ONE, 2012)
Land abandonment is one of the most powerful global change drivers in developed countries where recent rural exodus has been the norm. Abandonment of traditional land use practices has permitted the colonization of these areas by shrub and tree species. For fleshy fruited species the colonization of new areas is determined by the dispersal assemblage composition and abundance. In this study we showed how the relative contribution to the dispersal process by each animal species is modulated by the environmental heterogeneity and ecosystem structure. This complex interaction caused differential patterns on the seed dispersal in both, landscape patches in which the process of colonization is acting nowadays and mature woodlands of Juniperus thurifera, a relict tree distributed in the western Mediterranean Basin. Thrushes (Turdus spp) and carnivores (red fox and stone marten) dispersed a high amount of seeds while rabbits and sheeps only a tiny fraction. Thrushes dispersed a significant amount of seeds in new colonization areas, however they were limited by the presence of high perches with big crop size. While carnivores dispersed seeds to all studied habitats, even in those patches where no trees of J. thurifera were present, turning out to be critical for primary colonization. The presence of Pinus and Quercus was related to a reduced consumption of J. thurifera seeds while the presence of fleshy fruited shrubs was related with higher content of J. thurifera seeds in dispersers’ faeces. Therefore environmental heterogeneity and ecosystem structure had a great influence on dispersers feeding behaviour, and should be considered in order to accurately describe the role of seed dispersal in ecological process, such as regeneration and colonization. J. thurifera expansion is not seed limited thanks to its diverse dispersal community, hence the conservation of all dispersers in an ecosystem enhance ecosystems services and resilience.